Transcriptional autorepression of Msx1 gene is mediated by interactions of Msx1 protein with a multi-protein transcriptional complex containing TATA-binding protein, Sp1 and cAMP-response-element-binding protein-binding protein (CBP/p300) - SHETTY, Sheetal; TAKAHASHI, Takayuki; MATSUI, Hideo; AYENGAR, Rekha; RAGHOW, Rajendra (Biochemical journal, 1999)
The TATA-less murine Msx1 promoter contains two Msx1-binding motifs, located at -568 to -573 and +25 to +30, and is subject to potent autorepression [Takahashi, Guron, Shetty, Matsui and Raghow (1997) J. Biol. Chem. 272, 22667-22678]. To investigate the molecular mechanism by which Msx1 represses the activity of its own promoter, we transfected C2C12 myoblasts with Msx1-promoter-luciferase constructs and assessed reporter gene activity, with and without the exogenous expression of Msx1. We demonstrate that Msx1-mediated autorepression remained unaffected, regardless of the presence or absence of the Msx1 recognition motifs on the promoter. Furthermore, graded exogenous expression of TATA-binding protein (TBP), Sp1 or cAMP-response-element-binding protein-binding protein (CBP/p300) could counteract the autoinhibitory activity of Msx1. Finally, we demonstrate that Msx1 protein can be immunoprecipitated in a multiprotein complex containing TBP, Sp1 and CBP/p300. We hypothesize that the interaction of Msx1 protein with one or more ubiquitous or tissue-restricted transcription factors mediates transcriptional autorepression of the Msx1 gene.